Exploring the Course ideological and political education of the Writing Module "Communicating China’s Stories in English" for Vocational College Students - Chen Liang; Xu Chuang; Kai Yuanyuan (Journal of Exploration of Vocational Education, 2025)
Finding an effective integration point between course ideological and political education and English professional training is an important research topic. However, empirical studies in this area are still weak. This study focuses on vocational college students in Anhui Province and uses English writing courses on telling China’s stories as an example. It analyzes how to integrate ideological and political education into English writing teaching, particularly in writing materials and topic selection. By examining students’ writing texts, the writing process, post - writing reflections, peer evaluations, syllabus design and practice, and joint evaluations by teachers both inside and outside the school, the study aims to demonstrate the effect of the three - pronged nurturing in English writing classes. It also seeks to provide suggestions for integrating civic elements into English teaching programs and for comprehensive and holistic education in the future.